Performance Management: A Study Of Sales Incentive Scheme Implementation In Telekom Malaysia (M) - Mohamad Najid, Nur Najwa (2008)
This paper looks into how an organization such as Telekom Malaysia(TM), specifically , manages its sales employees' performance by proposing incentive schemes as alternatives to the traditional performance ranking system.